2014
DOI: 10.1002/cmdc.201402004
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Intercalation and Coordination of a Dirhodium Complex to DNA: Dual DNA Binding

Abstract: Two new complexes, cis-H,H-[Rh2 (OCCH3 NH)2 (LL)(CH3 CN)2 ](2+) , where LL=bpy (2, bpy=2,2'-bipyridine) and dppz (3, dppz=dipyrido[3,2-a:2',3'-c]phenazine), were prepared from the reaction of cis-H,H-[Rh2 (OCCH3 NH)2 (CH3 CN)6 ](2+) (1) with the corresponding bidentate ligand. The bpy and dppz ligands chelate to the same rhodium atom and are positioned trans to the amidato N atoms, as determined by the single crystal X-ray structure of 2. Irradiation of 2 and 3 with visible light in water results in the exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…The peak at ~520 nm apparent in 1 (ε ~ 200 M −1 cm −1 ) is characteristic of the Rh 2 (δ*)/amidato(π*)→Rh 2 (σ*) transition, also present in the related complex cis -H,H-[Rh 2 (OCCH 3 NH) 2 (bpy)(CH 3 CN) 2 ] 2+ (ε ~ 160 M −1 cm −1 ). This peak is also expected in 2 , but it cannot be observed due to the overlapping, intense tail of the 1 LC and 1 MLCT transitions [17,21,22]. …”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The peak at ~520 nm apparent in 1 (ε ~ 200 M −1 cm −1 ) is characteristic of the Rh 2 (δ*)/amidato(π*)→Rh 2 (σ*) transition, also present in the related complex cis -H,H-[Rh 2 (OCCH 3 NH) 2 (bpy)(CH 3 CN) 2 ] 2+ (ε ~ 160 M −1 cm −1 ). This peak is also expected in 2 , but it cannot be observed due to the overlapping, intense tail of the 1 LC and 1 MLCT transitions [17,21,22]. …”
Section: Resultsmentioning
confidence: 90%
“…Cis - [Rh 2 (OCCH 3 NH) 2 (CH 3 CN) 6 ](BF 4 ) 2 [21], dppn [33], and 1 [22] were synthesized according to published procedures. D 2 O (99.9% D) and 3-(trimethylsilyl)-1-propanesulfonic acid sodium salt (DSS) was purchased from Sigma Aldrich, whereas ethidium bromide (EtBr), 1,3- diphenylisobenzofuran (DPBF), and polystyrene sulfonate (PSS) were obtained from Aldrich and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Moreover, the related complexes cis - H,H -[Rh 2 (OCCH 3 NH) 2 (L)(CH 3 CN) 2 ] 2+ , where L = 2,2′-bipyridine (bpy, 1 ) or dipyrido[3,2- a :2′,3′- c ]phenazine (dppz, 2 ), depicted in Figure 1, coordinate to DNA upon photoinduced CH 3 CN exchange when irradiated in H 2 O and, in the case of 2 , also intercalate between the base pairs of the duplex. 37 This dual activity of 2 is of interest because compounds with novel DNA binding modes, such as simultaneous intercalation and coordination, have been shown to overcome cisplatin resistance. 38,39 The light activated intercalation and covalent DNA binding with 2 provides spatiotemporal control not available with the previous dual-binding platinum compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that both complexes undergo photoinduced covalent binding to the 12-mer duplex oligonucleotide d(5′-CTCTCAACTTCC-3′)•d(5′-GGAAGTTGAGAG-3′), but 2 also exhibits enhanced intercalation following irradiation. 37 To elucidate the specific binding sites of 1 and 2 , 2D 1 H− 1 H NOESY and thermal denaturation experiments were conducted with the shorter d(GTCGAC) 2 duplex both in the dark and upon irradiation with visible light.…”
Section: Introductionmentioning
confidence: 99%